2013
DOI: 10.1128/iai.00125-13
|View full text |Cite
|
Sign up to set email alerts
|

The Trypanosoma brucei gambiense Secretome Impairs Lipopolysaccharide-Induced Maturation, Cytokine Production, and Allostimulatory Capacity of Dendritic Cells

Abstract: bTrypanosoma brucei gambiense, a parasitic protozoan belonging to kinetoplastids, is the main etiological agent of human African trypanosomiasis (HAT), or sleeping sickness. One major characteristic of this disease is the dysregulation of the host immune system. The present study demonstrates that the secretome (excreted-secreted proteins) of T. b. gambiense impairs the lipopolysaccharide (LPS)-induced maturation of murine dendritic cells (DCs). The upregulation of major histocompatibility complex class II, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
2
14
1
Order By: Relevance
“…The hallmarks of this effect were an inhibition of the LPS‐induced CD83 and HLA‐DR expression, whereas expression of costimulatory molecules and C‐type lectin receptors was not modified. This contrasts with a previous study which found that trypanosome secretome exerts a suppressive activity on LPS‐stimulated murine DCs by inhibiting both the expression of CD80, CD86, CD40 and MHC class II molecules . These differences could be partly explained by the influence of the specificity of the immune response according to different hosts .…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…The hallmarks of this effect were an inhibition of the LPS‐induced CD83 and HLA‐DR expression, whereas expression of costimulatory molecules and C‐type lectin receptors was not modified. This contrasts with a previous study which found that trypanosome secretome exerts a suppressive activity on LPS‐stimulated murine DCs by inhibiting both the expression of CD80, CD86, CD40 and MHC class II molecules . These differences could be partly explained by the influence of the specificity of the immune response according to different hosts .…”
Section: Discussioncontrasting
confidence: 91%
“…These differences could be partly explained by the influence of the specificity of the immune response according to different hosts . The resulting cytokine profiles reported by Garzon et al were, however, rather similar to those in our study, with inhibition of cytokines with both inflammatory (TNF‐α) and counter‐inflammatory (IL‐10) properties. This contrasts with some data from clinical settings.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…This may represent a rapid way of remodeling the surface upon environmental changes without activating protein degradation pathways [75]. It could also represent a mechanism for signaling and regulation of the interaction between parasites and with the host cells [107, 106]. …”
Section: Future Challenges and Conclusionmentioning
confidence: 99%